Kyrgyzstan under Covid-19: Government’s Response to Food Insecurity, Hunger and Poverty (International Journal of Food and Nutritional Sciences, 2022)
AbstractThis article aims to shed light on the linkages between food insecurity, poverty and hunger by highlighting their interconnectedness and the role of various actors in addressing these challenges in Kyrgyzstan. It will examine how Kyrgyzstan’s situation was before and after COVID-19. Both direct and indirect repercussions of COVID-19 mitigation strategies have served to heighten pre-existing risks, preventing people especially children and adolescents from reaching their full capabilities. This study aimed to assess the prevalence of various issues like Poverty, hunger and food insecurity faced by Kyrgyzstan. Findings highlight that the pandemic has also led to magnify issues like food insecurity, health issues, hunger, poverty etc. in Kyrgyzstan.